Prophylactic antibiotics in patients with episiotomy following normal vaginal delivery: a randomised clinical trial - Garala, Nirav J.; Nambiar, Sabnam S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Postpartum infectious complications following normal vaginal delivery remains a cause of major concern for the health care professionals due to higher morbidity and mortality and prolonged hospital stays and increased healthcare costs which makes us consider prophylactic use of antibiotics after normal vaginal delivery. On the other hand unjudicious use of antibiotics has led to widespread antibiotic resistance. Therefore this study was carried out to validate the use of prophylactic antibiotics in these patients and their role in prevention of puerperial pyrexia, wound infections and prolonged hospital stay. Methods: This Randomised clinical trial was conducted at KCHC-Kerala Co-operative Hospital Complex, Pariyaram, Kannur District, Kerala from 1st March 2012 to 30th April 2013. Eligible women were randomly assigned to group which does not receive prophylactic antibiotics (Group A) and group receiving prophylactic antibiotics (Group B). Patients in both the groups were examined every day till the patient was discharged from the hospital and observed for signs and symptoms of infected episiotomy wound, puerperial pyrexia and duration of hospital stay was noted. Results: Mean age in years was 25.6 for Group A and 26.2 for Group B. Mean gestational age in both the groups was 37.6 weeks. Mean duration of labour was 6.62 and 6.22 hours for Group A and B respectively. 6 subjects in Group A and 5 subjects in Group B had puerperial pyrexia. 3 Subjects in Group A and 2 subjects in Group B had wound infection. The mean duration of hospital stay for Group A was 4.18 with SD of 1.0 while mean hospital stay for Group B was 4.01 with SD of 1.1. Conclusions: By comparing subjects in both the groups with respect to puerperial pyrexia, wound infection and duration of hospital stay there was no statistical difference in any of the above criteria in both groups. Hence, in view of the risk of allergic reactions, toxicity and the selection of resistant strains the prophylactic administration of antibiotics does not seem to be justified in patients with episiotomy following vaginal delivery as per this study.